Saperci fare nel rapporto uomo-animale. Il contributo antropologico sulla salvaguardia della biodiversità - Lorenzoni, Flavio; Padiglione, Vincenzo; Quadraccia, Daniele (Antropologia Pubblica, 2024)
On a global scale, the current political agenda is focusing ever more on the consequences of human actions on the environment and on the need to consider and suggest new ways to interact with our planet. While the green message has acquired a global reach, it seems new theories arise among the human sciences and political discourses when the carbon footprint becomes too evident to be ignored. In this dichotomy of excitement for new possibilities and the state of the emergency of our ecosystem, the anthropological debate calls for multifocal ethnographies and a glocal view capable of highlighting specific contexts to the point of being able to rethink the concept of “living” and “person”. Analysing the experience of the ethnographic research known as “Saperci Fare" – conducted by a team of anthropologists in collaboration with various institutions – the findings give cause for reflection on the ongoing debate regarding the anthropology of biodiversity and the human-animal relationship, wondering what role local knowledge and know-how play in today’s society in the fight to preserve biodiversity, communities and places. All in the name of preserving different individual memories broadening the horizon for what concern theoretical and methodological studies pioneered by ontological authors.